Association of USF1 and APOA5 polymorphisms with familial combined hyperlipidemia in an Italian population. Issue 1 (February 2015) - Di Taranto, Maria Donata; Staiano, Antonino; D'Agostino, Maria Nicoletta; D'Angelo, Antonietta; Bloise, Elena; Morgante, Alberto; Marotta, Gennaro; Gentile, Marco; Rubba, Paolo; Fortunato, Giuliana
Abstract: Background: Familial combined hyperlipidemia (FCH) is a polygenic and multifactorial disease characterized by a variable phenotype showing increased levels of triglycerides and/or cholesterol. The aim of this study was to identify single nucleotides (SNPs) in lipid-related genes associated with FCH. Methods and results: Twenty SNPs in lipid-related genes were studied in 142 control subjects and 165 FCH patients after excluding patients with mutations in the LDLR gene and patients with the E2/E2 genotype of APOE. In particular, we studied the 9996G > A (rs2073658) and 11235C > T (rs3737787) variants in the Upstream Stimulatory Factor 1 gene (USF1), and the −1131T > C (rs662799) and S19W (rs3135506) variants in the Apolipoprotein A-V gene (APOA5). We found that the frequencies of these variants differed between patients and controls and that are associated with different lipid profiles. At multivariate logistic regression SNP S19W in APOA5 remained significantly associated with FCH independently of age, sex, BMI, cholesterol and triglycerides. Conclusions: Our results show that the USF1 and APOA5 polymorphisms are associated with FCH and that the S19W SNP in the APOA5 gene is associated to the disease independently of total cholesterol, triglycerides and BMI. However, more extensive studies including other SNPs such as rs2516839 in USF1, are required.